Reproducible Audio Chaotic Masking With a Chua-Type Oscillator and Key-Sensitivity Analysis: Online First: 12/05/2026 - Phan, Thi Tuoi; Nguyen, Vu Thang; Phan, Anh Tuan; Pham, Duc Hung (Journal of Technical Education Science, 2026)
This paper presents a reproducible software-based demonstration of audio chaotic masking using a Chua-type chaotic oscillator. A discrete chaotic keystream is generated by numerically integrating a nonlinear ordinary differential equation with the ode45 solver, using sample-aligned short-interval integration. The recorded audio signal is encrypted through linear additive masking with a scaled chaotic state sequence and recovered by subtracting an identically regenerated sequence using the same system parameters and initial conditions. The study emphasizes the sensitivity of decryption accuracy to key mismatch, where even slight perturbations of the initial condition lead to significant reconstruction degradation. Quantitative evaluation metrics including normalized RMSE, reconstruction SNR, and correlation coefficient are employed to assess masking effectiveness and recovery fidelity. The proposed implementation serves as a transparent and replicable educational baseline for chaos-based communication research, while also highlighting the inherent security limitations of simple additive chaotic masking schemes.